Pengaruh Model Project Based Learning Berbasis STEAM melalui Kegiatan outdoor pada Materi Ekosistem untuk Meningkatkan Kreativitas Siswa Kelas X SMA Budi Luhur Samarinda - Dinfisa Putri Mindi Sahara; Vandalita Maria Magdalena Rambitan; Sonja Verra Tinneka Lumowa; Herliani; Sri Purwati (PendIPA Journal of Science Education, 2026)
The purpose of this research was to assess the impact of the STEAM-based PjBL model on the creativity of class X pupils at SMA Budi Luhur Samarinda in relation to ecology topics through outdoor activities. The methodology of this investigation was quasi-experimental and used a posttest-only control group approach. The study sample included 50 pupils, specifically class X-2, which used the STEAM-based PjBL approach through outdoor activities as the experimental class, and class X-1, which employed the PBL model as the control class. The sample was selected using a purposive sampling approach. A creativity observation rubric with markers for fluency, flexibility, originality elaboration, and individual contribution served as the research instrument. The SPSS version 25 was used to conduct data analysis, including hypothesis tests, normality tests, and homogeneity tests, utilizing independent sample t-tests. The study found that the average score for student creativity in the experimental group was 88.16, but the control group's score was 78.60. A hypothesis test yielded a significance value (Sig. 2-tailed) of 0.000 <0.05, leading to the rejection of H0 and the acceptance of Ha. Therefore, it may be deduced that the STEAM-based PjBL model has a considerable impact on the creativity of class X students at SMA Budi Luhur Samarinda when it comes to ecosystem content through outdoor activities.